Expectations of mining companies and the needs of mining communities in South Africa - Mabikwa, Nomathemba (My University, 2018)
This research study focused on identifying the gap between the expectations of mining companies and communities in relation to development and social responsibility. This qualitative research study focused on trying to understand the alignment or misalignment of the different stakeholder’s expectations. This study was relevant; first, given the recent community unrest in the mining communities; and second, because of the Department of Mineral Resources’ (DMR) focus on community development around the mining towns, with particular emphasis on mines being expected to uplift the communities around the mines. Identifying the gap between their respective expectations would be beneficial for both the communities as well as the mining companies. The benefit to the communities would come in the form of relevant development and assistance being given to the communities. Another benefit would be to the mining companies who face community unrest, yet do not understand the communities’ needs. The research methodology was qualitative; data was collected through interviews with Pilanesburg Platinum Mines (PPM) mine management, questionnaires distributed to community leaders, community influencers and ordinary community members, and semi-structured interviews with activists and mine representatives of other mines. This allowed the identification of further stakeholders that were not in the original proposal. The ordinary community members, randomly selected to understand grassroots expectations, implied that the decisions made by community leaders were not necessarily representative of the community’s needs. The study found that some of the expectations from community leaders were different to those of the activists. Community leaders expected mines to focus on building schools, hospitals, and roads, developing skills, and giving business opportunities to community members, while activists were more concerned about environmental issues, land degradation, pollution of water and air, as well as rehabilitation of the land after the mine had used it. Similarly, the study identified that the government, represented by the DMR, expected the mines to develop the communities, as stipulated in the mines’ SLPs. The mine representatives of other mines experienced unrest in their communities similar to that which was happening at PPM. PPM management, on the other hand, felt that community leaders should have a clear understanding of business processes so as to avoid production disruptions caused by community unrest. Management were of the opinion that proper structures in the community should be formed and used to address issues with the mines. It is clear from the study that the communication between the different stakeholders can assist in closing the gap between the communities’ and mines’ expectations. This in turn would prevent community unrest and subsequent road closures, and enable the mines to operate profitably, and offer employment and development opportunities to the community. Recommendations for each stakeholder group are made in this regard. This research article is inclusive of the requirements of The Journal of the Southern African Institute of Mining and Metallurgy (SAIMM)
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2018
Keywords: Mines and mineral resources--South Africa; Miners--Dwellings--South Africa; Mining districts--South Africa